Best Practice: Waste to Fertilizer in Polytechnic Mersing - Ts. Murugan Krishnan (Universitas Diponegoro, 2022)
Institutions of Higher Learning in Malaysia which serve as an educational and research institution need to emphasize on sustainability issues to ensure continuous efforts. However, acceptance from campus staff makes it difficult for these sustainability efforts to continue due to the lack of strong support and high awareness of the importance of caring for the environment. The purpose of this study was to provide knowledge and awareness on food waste can be used as fertilizer. These composite fertilizers are then used in agricultural activities at polytechnics to generate income. The knowledge and awareness of sustainability is very high among campus residents. However, the practice and willingness to be involved in the implementation is at a low level and needs to design more awareness programs and activities that are more interesting to campus residents so that sustainability practices can become a culture in their daily lives.Keyword: Awareness on sustainability, sustainability practice and food waste and waste to fertilizer